The Entente’s Support for the White Armies in Southern Russia (Late 1918–1919) - G. G. Popov; T. G. Chshiev; O. Yu. Kazenkov (Vestnik MGIMO-Universiteta)
This article examines a previously underexplored aspect of the Russian Civil War during its critical phase in late 1918–1919: the logistical support provided by the Entente to the White armies in the South, set against the backdrop of the final military interventions. The authors concentrate on the interactions between General A.I. Denikin's regime and the British authorities, who were the primary proponents of the Entente's intervention in Russia, as well as the conditions surrounding the involvement of the French armed forces.The research primarily draws on documents from the Russian State Military Archive, created by officers of the White armies of Southern Russia, and the National Archives of Great Britain. This comprehensive source base enables a reassessment of some long-held views in Russian historiography regarding the Entente's intervention in the Black Sea region. The study aims to delineate the scope and nature of the Entente’s support and to understand why this assistance failed to secure a victory for the White forces.Post-Soviet historiography commonly posits that the Red Army enjoyed an economic advantage in terms of weapons and ammunition supply for most of the Civil War. This article, however, reveals that the support from Entente countries was substantial and that the use of foreign weapons and equipment significantly influenced the late 1918-1919 period. Nonetheless, the critical factor, as argued by the authors, was the timing of deliveries. The peak of the Entente’s military-technical support to the Armed Forces of Southern Russia occurred after the Red Army had already fortified its positions with adequate firepower. The lengthy strategic decision-making processes of the British Cabinet, characteristic of British democratic and bureaucratic systems, resulted in delayed assistance to Denikin’s troops, ultimately undermining its effectiveness.